2019
DOI: 10.1021/acssuschemeng.8b04465
|View full text |Cite
|
Sign up to set email alerts
|

Nanosilver Coated Coir Based Dielectric Materials with High K and Low Df for Embedded Capacitors and Insulating Material Applications–A Greener Approach

Abstract: In this work, the dielectric properties of lignocellulosic coirs coated with silver nanoparticles were studied. Nanosilver coating increased the dielectric constant (K) value and decreased the dissipation factor (Df). The increase in dielectric constant of the nanocomposite could be assigned to the stacking of charges at the extended interface of the synthesized nanocomposites. In the present study, a significant decrease in Df was witnessed which could be due to the well-established quantum effect of metal na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Ceramic/polymer , and conductor/polymer , composites are commonly used as dielectric materials for embedded capacitors. A large number of researches have shown that even if the amount of ceramic reaches 50 vol % or even higher, it is difficult for ceramic/polymer composites to achieve dielectric permittivity exceed 100. Differently, a low loading of conductors can endow the polymer composite with higher dielectric permittivity; however, they also bring nonlinear increase in dielectric loss , and reduction in breakdown strength. , Both low dielectric permittivity and breakdown strength cause a greatly reduced energy density, so ceramic/polymer and conductor/polymer composites limit the possibility to fabricate high performance embedded capacitors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ceramic/polymer , and conductor/polymer , composites are commonly used as dielectric materials for embedded capacitors. A large number of researches have shown that even if the amount of ceramic reaches 50 vol % or even higher, it is difficult for ceramic/polymer composites to achieve dielectric permittivity exceed 100. Differently, a low loading of conductors can endow the polymer composite with higher dielectric permittivity; however, they also bring nonlinear increase in dielectric loss , and reduction in breakdown strength. , Both low dielectric permittivity and breakdown strength cause a greatly reduced energy density, so ceramic/polymer and conductor/polymer composites limit the possibility to fabricate high performance embedded capacitors.…”
Section: Introductionmentioning
confidence: 99%
“…Ceramic/polymer 7,8 and conductor/polymer 9,10 composites are commonly used as dielectric materials for embedded capacitors. A large number of researches have shown that even if the amount of ceramic reaches 50 vol % or even higher, it is difficult for ceramic/polymer composites to achieve dielectric permittivity exceed 100.…”
Section: Introductionmentioning
confidence: 99%